Policy Networks, Philanthropy, and Education Governance in Portugal: The Raise of Intermediary Actors - Viseu, Sofia (2021)
This article focuses on an emerging phenomenon in Portugal: the most visible and frequent presence of new collective actors in public policy processes. Often linked to philanthropic foundations, these actors call themselves to influence the educational agenda, and even the educational practices, and are highly dependent on expert knowledge. They are intermediary actors who perform cognitive and social operations that connect ideas, individuals and technical devices involved in policy processes. The article analyses the emergence of these intermediary actors and their attempts to influence and reshape the governance of education, through new political networks. Based on earlier empirical-based research inspired by network ethnography, and grounded on the political sociology of public action, the article presents a proposal for mapping these emerging intermediary actors, according to a) the spaces of collective action they use/create; b) their targets; c) their autonomy in the production of expert knowledge for policy. And depicts two trends related to their agency: the use of a more cognitive (rather than normative) regulation, more intensive and knowledge-based, converging to a new interactive and intuitive ways of knowledge dissemination; an increasingly intertwined regulation, involving several different social worlds, promoting and establishing new policy networks and the spread of the new philanthropy reasoning.